Experimental investigation on the thermal performance of heat pipe solar collector (HPSC). (2020) - Jayanthi, N.; Suresh Kumar, R.; Karunakaran, Gopalu; Venkatesh, M.
Abstract: In this work an experimental study is made to find out the thermal performance of heat pipe solar collector (HPSC) using distilled water and R134a as working fluid. The HPSC is fabricated from the copper tube with the outer diameter of 58 mm and length of 1800 mm. The experimental work is carried out under different operating conditions. The input parameters such as temperature distribution and time on the thermal efficiency of the HPSC were investigated, compared and discussed. From the results, it is observed that the efficiency of the HPSC increases when R134a was used instead of distilled water.